Sensory Evaluation of Instant Drink Red Guava (Psidium guajava L.) Using the Ranking Method - Silvi Widayanti; Syarifa Ramadhani Nurbaya (Universitas Muhammadiyah Sidoarjo, 2022)
Red guava is a fruit that is in great demand by consumers because it is nutritious for the health of the body. Red guava is widely used for juice or eaten fresh. However, fresh guava fruit and guava juice cannot be stored for long, because they have a high water content. Therefore, it is necessary to carry out further treatment so that nutritional needs can be maintained and can be extended by making instant drink powder using the foam mat drying method. The main purpose of this research is to produce instant powder drink that can be accepted by respondents and to know the level of respondent's preference for red guava juice. The method in this study uses the ranking test method. The panelists in the study were students of the Muhammadiyah University of Sidoarjo who opened 30 people. Instant drink of red guava juice with a ratio of red guava powder with a sucrose concentration of 10%, 20%, and 30% with a proportion of water 1:5, 1:10 and 1:15. It can be said that there is a significant effect on the aroma, taste, texture and color as well as the level of respondent's preference for the red guava juice drink produced. Sensory data were statistically analyzed using one-way ANOVA. If it shows a significant result, then it is continued with a significant difference test using Duncan's Multiple Range Test (DMRT) at a significance level of 0.05. The results showed that there were significant differences in each treatment.